Anti-doping policy: : A comparative study of implementation in Iceland and Denmark - Gunnarsson, Torgils (Malmö universitet, Institutionen Idrottsvetenskap (IDV), 2021)
This study investigates the differences and similarities in implementation of anti-doping policy in Denmark and Iceland. Various anti-doping themes has been chosen to dig deeper into the implementation on policies between the two countries which are related to: Economy, Education, Testing and Investigation, International Cooperation, Fitness and Public Health and Research and Development. A comparison of the implementation is done where governance and power within anti-doping is analyzed in the countries. The aim is to outline the ways the two countries implement anti-doping policy, analyze how their NADOs are governed as well as how power and interconnections are divided between the stakeholders of anti-doping. Document analysis and a semi structured interview was conducted in order to collect the data needed for the investigation and analysis process. A thematic analysis was developed to be able to gather the most vital and reliable data on the selected anti-doping themes. Additionally, theory on power, interconnections and good governance was implemented to reach towards the purpose of this study. The analysis showed different outcomes in the two countries. Denmark implements the international anti-doping policy to a high degree where they adapt to it in relation to national strategies in sport. Iceland has difficulties in adapting to every anti-doping standard of the international policy and focuses on the ones of most importance to Icelandic sport and society. The study concluded that both countries implement and comply to the international anti-doping policy by law and have independent NADOs that are responsible for anti-doping nationally. Despite complying to the international law, the implementation differs in the countries which is affected by national prioritization and resources. The main focus of Iceland is education and testing where Denmark is more developed within their NADO and prioritizes every standard to a certain degree. The NADOs are steered by the policies set by WADA and their governments ...